Understanding the Transient Nature of STEM Doctoral Students’ Research Self-Efficacy Across Time: Considering the Role of Gender, Race, and First-Generation College Status - Litson, Kaylee; Blaney, Jennifer M.; Feldon, David F. (Frontiers in Psychology, 2021)
Developing research self-efficacy is an important part of doctoral student preparation. Despite the documented importance of research self-efficacy, little is known about the progression of doctoral students’ research self-efficacy over time in general and for students from minoritized groups. This study examined both within- and between-person stability of research self-efficacy from semester to semester over four years, focusing on doctoral students in biological sciences (N = 336). Using random intercept autoregressive path analyses, we evaluated differences in stability across gender, racially minoritized student status, and first-generation student status. Results showed similar mean levels of self-efficacy across demographic groups and across time. However, there were notable differences in between-person and within-person stability over time, specifically showing higher between-person and lower within-person stability for racially minoritized and first-generation students. These findings indicate that racially minoritized and first-generation students’ research self-efficacy reports were less consistent from semester to semester. Such results may indicate that non-minoritized and continuing-generation students’ experiences from semester to semester typically reinforce their beliefs about their own abilities related to conducting research, while such is not the case for racially minoritized nor first-generation students. Future research should examine what types of experiences impact self-efficacy development across doctoral study to offer more precise insights about factors that influence these differences in within-person stability.